2020
DOI: 10.1155/2020/9343160
|View full text |Cite
|
Sign up to set email alerts
|

Light Emitting Diode Therapy Protects against Myocardial Ischemia/Reperfusion Injury through Mitigating Neuroinflammation

Abstract: Background. Neuroinflammation plays a key role in myocardial ischemia-reperfusion (I/R) injury. Previous studies showed that light-emitting diode (LED) therapy might improve M2 microglia activation and brain-derived neurotrophic factor (BDNF) expression, thereby exerting anti-inflammatory effects. Therefore, we hypothesized that LED therapy might reduce myocardial I/R injury by neuroinflammation modulation. Objective. To explore the effect of LED therapy on myocardial I/R-induced injury and seek the underlying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
(43 reference statements)
0
10
0
Order By: Relevance
“…Recently, our studies showed that LED therapy (2.0 J/cm 2 , 610 nm) located at the skull surface of the hypothalamic PVN through the scalp and skull from 30 min before ischemia to 3 h after reperfusion could significantly attenuate the ischemia and infarct size following cardiac I/R. 90 In addition, LED illumination significantly reduced the inducibility of ventricular arrhythmias after I/R injury. The attenuated activation of microglia and subsequently decreased peripheral sympathetic activity contribute to the protective effects of LED therapy against cardiac I/R injury.…”
Section: The Potential Role Of Microglia In Cardiovascular Diseasesmentioning
confidence: 90%
See 1 more Smart Citation
“…Recently, our studies showed that LED therapy (2.0 J/cm 2 , 610 nm) located at the skull surface of the hypothalamic PVN through the scalp and skull from 30 min before ischemia to 3 h after reperfusion could significantly attenuate the ischemia and infarct size following cardiac I/R. 90 In addition, LED illumination significantly reduced the inducibility of ventricular arrhythmias after I/R injury. The attenuated activation of microglia and subsequently decreased peripheral sympathetic activity contribute to the protective effects of LED therapy against cardiac I/R injury.…”
Section: The Potential Role Of Microglia In Cardiovascular Diseasesmentioning
confidence: 90%
“… Inhibition of TLR4 attenuated sympathoexcitation. [ 84 ] Sprague–Dawley rats (250–300 g) Ligation of the LAD for 30 min and reperfusion for 3 h LED light source (610 nm) illumination LED illumination significantly inhibited LSG neural activity and decreased microglia activation and the levels of IL-1β, TNF-α and NGF LED therapy reduced microglia activation and pro-inflammatory cytokine expression after cardiac I/R [ 90 ] Abbreviations : MI, myocardial infarction; FRA, fos-related antigens; IVP, intraventricular pressure; LVEDP, left ventricular end-diastolic pressure; NLRP3, NOD-like receptor protein 3; RSNA, renal sympathetic nerve activity; TLR4, Toll-like receptor 4; NF-κB, nuclear factor kappa-B; LAD, left anterior descending; I/R, ischemia/reperfusion; LED, light emitting diode; NGF, nerve growth factor. …”
Section: The Potential Role Of Microglia In Cardiovascular Diseasesmentioning
confidence: 99%
“…Studies have shown that many cardiovascular diseases, such as MI, HF and hypertension, are characterized by reduced cardiac function due to peripheral inflammation associated with increased central sympathetic tone, while neuroinflammation of the PVN in turn leads to increased central sympathetic tone. 4 Under hypertensive conditions, the PVN activates and releases NE, 23 an excitatory neurotransmitter, thereby promoting sympathetic output. 24 , 25 In studying diseases such as memory impairment and neurological damage after cerebral ischaemia‐reperfusion, animal models of cerebral ischaemic stroke reflect that the TLR4/MyD88/NF‐kB axis is involved in neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroinflammation in the paraventricular nucleus (PVN) of the hypothalamus is a key factor in increased sympathetic activity, which is the basis for the pathogenesis of many cardiovascular diseases, including MI. 3 , 4 Numerous studies have shown that acute myocardial infarction (AMI) induces an early inflammatory response, resulting in a neuroinflammatory response and oxidative stress within the PVN, which leads to neuronal excitation within the PVN and the promotion of stellate ganglion (STG) remodelling and inflammatory infiltration, eventually leading to cardiac sympathetic excitation. 5 , 6 , 7 , 8 However, the exact mechanism of how PVN induces sympathetic excitation and ultimately leads to VAs in the heart is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…These, then produce dynamic shear stress, hydrostatic pressure, mechanical modulation of SCs, and tailored diffusivity (Adamo and García-Cardeña, 2011;Estrada et al, 2011;Ali et al, 2020). In addition, biophysical cues, such as optic and magnetic/electric, could be provided to culture chambers to further influence SCs fate (Wang et al, 2020). This consequently minimize the use of expensive biochemical signals.…”
Section: Microfluidic Systems/bioreactors/organ-on-a-chip and Irimentioning
confidence: 99%